2012
DOI: 10.1002/yd.20008
|View full text |Cite
|
Sign up to set email alerts
|

ViSC Social Competence Program

Abstract: The ViSC Social Competence Program has been implemented in Austrian schools within the scope of a national strategy plan, Together Against Violence. The program is a primary preventive program designed for grades 5 to 8. The prevention of aggression and bullying is defined as a school development task, and the initial implementation of the program lasts one school year. The program consists of universal and specific actions that are implemented through in-school teacher training and a class project for student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 14 publications
0
43
0
1
Order By: Relevance
“…The present study aims at filling these gaps. Competence Training; see Strohmeier, Hoffmann, Schiller, Stefanek, & Spiel, 2012). Informed consent was obtained from parents and school officials.…”
Section: Construct Validity Of the Agg-iatmentioning
confidence: 99%
“…The present study aims at filling these gaps. Competence Training; see Strohmeier, Hoffmann, Schiller, Stefanek, & Spiel, 2012). Informed consent was obtained from parents and school officials.…”
Section: Construct Validity Of the Agg-iatmentioning
confidence: 99%
“…According to Strohmeier et al (2012), this program was effective in reducing bullying perpetration, but preliminary results showed that victimization rates did not change. There was a decrease in cyberbullying (perpetration and victimization) (Gradinger et al 2016) and detailed results regarding bullying are still being collected.…”
Section: Viennese Social Competence (Visc)mentioning
confidence: 79%
“…At the end, the students design a small project and thus work together to achieve a positive, common goal (for details see Atria & Spiel, 2007;Strohmeier, Hoffmann et al, 2012) and practice their social skills. ViSC is a primary preventive program including secondary preventive elements (i) to reduce aggressive behavior and bullying and (ii) to foster social and intercultural competencies in schools.…”
Section: The Visc Social Competence Programmentioning
confidence: 99%
“…The ViSC program is a primary preventive anti-bullying program that does not include specific anti-cyberbullying elements (Strohmeier, Hoffmann, Schiller, Stefanek, & Spiel, 2012). The ViSC program is a primary preventive anti-bullying program that does not include specific anti-cyberbullying elements (Strohmeier, Hoffmann, Schiller, Stefanek, & Spiel, 2012).…”
Section: Introductionmentioning
confidence: 99%